The spontaneous coping strategies of children who live with chronic pain : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Ramsay, Karen Elaine (Massey University, 1994)
The spontaneous coping strategies of children who experience chronic disease-related pain have received little research attention. Ten children aged between 7 and 13 years were interviewed. The interview data was analysed using the grounded theory method of qualitative data analysis. The participant children described using a variety of cognitive and behavioural coping strategies in order to manage their pain. The children also described changes over time in the types of coping strategies that they utilized. Most children also described subjective habituation to pain. A local theory was generated from the data which describes the changing process over time of the children's getting used to living with pain. Children's ways of being changed over time, along with their appraisals of pain and their use of coping strategies. Similarities between this process and strategies that have been found to be adaptive in the adult chronic pain literature were noted. Strategies that were pervasively described were cognitive-behavioural distractions and behavioural interventions. Coping strategies that have not been previously documented among children were also found. "Keeping going" was a purposefully used coping strategy, as was seeking social support and minimizing pain. The implications of these findings including the contexts which impact on use and effectiveness of the children's coping strategies are discussed.
Keywords: Pain in adolescence; Pain in children